Cell Type-Specific Transcriptomics of Lateral Root Formation and Plasticity - Kortz, Annika; Hochholdinger, Frank; Yu, Peng (Frontiers in Plant Science, 2019)
Lateral roots are a major determinant of root architecture and are instrumental for the efﬁcient uptake of water and nutrients. Lateral roots consist of multiple cell types each expressing a unique transcriptome at a given developmental stage. Therefore, transcriptome analyses of complete lateral roots provide only average gene expression levels integrated over all cell types. Such analyses have the risk to mask genes, pathways and networks specifically expressed in a particular cell type during lateral root formation. Cell type-specific transcriptomics paves the way for a holistic understanding of the programming and re-programming of cells such as pericycle cells involved in lateral root initiation. Recent discoveries advanced the molecular understanding of the intrinsic genetic control of lateral root initiation and elongation. Moreover, the impact of nitrate availability on the transcriptional regulation of lateral root formation in Arabidopsis and cereals has been studied. In this review, we will focus on the systemic dissection of lateral root formation and its interaction with environmental nitrate by cell type-specific transcriptome analyses. These novel discoveries provide a better mechanistic understanding of postembryonic lateral root development in plants.